2011
DOI: 10.1080/15504263.2011.568360
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Supported Employment in People With Dual Disorders

Abstract: Objective This study compared the effectiveness of the Individual Placement and Support (IPS) model of supported employment to control vocational rehabilitation programs for improving the competitive work outcomes of people with a severe mental illness and co-occurring substance use disorder. Methods A secondary data analysis was conducted drawing from four randomized controlled trials comparing IPS supported employment to conventional vocational rehabilitation programs for severe mental illness, and focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 50 publications
(62 reference statements)
2
24
0
3
Order By: Relevance
“…It should also be noted that IPS does not have a large evidence base for improving employment in a largely substance using, homeless population and research has primarily focused on clients with SMI. There is some evidence that IPS helps individuals with co-occurring mental health and substance use diagnoses achieve better employment outcomes than other vocational services [60][61]; however, IPS may be less advantageous for the population studied here, offering a possible explanation for the lack of significant findings in non-vocational outcomes between the groups. These findings may have also been influenced by the 70-72 percent follow-up rates, leading to a potential selection bias; differences may have gone unmeasured because of attrition, which may have confounded the comparison of groups.…”
Section: Discussionmentioning
confidence: 71%
“…It should also be noted that IPS does not have a large evidence base for improving employment in a largely substance using, homeless population and research has primarily focused on clients with SMI. There is some evidence that IPS helps individuals with co-occurring mental health and substance use diagnoses achieve better employment outcomes than other vocational services [60][61]; however, IPS may be less advantageous for the population studied here, offering a possible explanation for the lack of significant findings in non-vocational outcomes between the groups. These findings may have also been influenced by the 70-72 percent follow-up rates, leading to a potential selection bias; differences may have gone unmeasured because of attrition, which may have confounded the comparison of groups.…”
Section: Discussionmentioning
confidence: 71%
“…A recently published randomized controlled trial demonstrated that individual placement and support (IPS) programs (i.e., individualized rapid job searches, community-based job placement) were effective at increasing competitive employment among veterans with PTSD (Davis et al, 2012). Another study demonstrated that the IPS model improves work outcomes of dually diagnosed veterans (Mueser et al, 2011). More research is needed to determine whether employment-based programs can have positive effects on other health outcomes among veterans, including reductions in alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…We consider a potential effect of reducing the present unemployment rate by 60% based on the estimated effect as reported by Mueser et al 10 For instance, if the pre-effect unemployment rate of a minority group is 20%, the post-effect unemployment rate becomes 0.4*20%=8%.…”
Section: Results Of Simulation Amentioning
confidence: 99%